Heterogeneity of hypothalamic pro-opiomelanocortin-expressing neurons revealed by single-cell RNA sequencing - Brian Y.H. Lam; Irene Cimino; Joseph Polex-Wolf; Sara Nicole Kohnke; Debra Rimmington; Valentine Iyemere; Nicholas Heeley; Chiara Cossetti; Reiner Schulte; Luis R. Saraiva; Darren W. Logan; Clemence Blouet; et al. (Elsevier, 2017)
Objective: Arcuate proopiomelanocortin (POMC) neurons are critical nodes in the control of body weight. Often characterized simply as direct targets for leptin, recent data suggest a more complex architecture. Methods: Using single cell RNA sequencing, we have generated an atlas of gene expression in murine POMC neurons. Results: Of 163 neurons, 118 expressed high levels of Pomc with little/no Agrp expression and were considered "canonical" POMC neurons (P+). The other 45/163 expressed low levels of Pomc and high levels of Agrp (A+P+). Unbiased clustering analysis of P+ neurons revealed four different classes, each with distinct cell surface receptor gene expression profiles. Further, only 12% (14/118) of P+ neurons expressed the leptin receptor (Lepr) compared with 58% (26/45) of A+P+ neurons. In contrast, the insulin receptor (Insr) was expressed at similar frequency on P+ and A+P+ neurons (64% and 55%, respectively). Conclusion: These data reveal arcuate POMC neurons to be a highly heterogeneous population.Accession Numbers: GSE92707. Author Video: Author Video Watch what authors say about their articles Keywords: POMC, Melanocortin, AGRP, Leptin, Insulin, Hypothalamus, Arcuate nucleus, Gene expression, Neuron, Transcriptome